PENDAMPINGAN PELAKSANAAN PEMBANGUNAN DAN PENATAAN MAKAM KATOLIK GIRIGONDO DI PURWOKERTO BANYUMAS (Universitas Wijayakusuma Purwokerto, 2023)
Life will end in death. Likewise with humans, will definitely die. This is a natural reality attached to humans that cannot be avoided. Death as the end of life is respected and remembered by family, relatives, relatives and the surrounding community who knew the human when he lived. To respect and remember, it takes a final resting place called a tomb. Girigondo is a public burial place, namely an area of land that is provided for the purposes of burial for everyone without distinguishing between groups, which is managed by the Cathedral Church of Christ the King, Purwokerto. As a burial facility intended for Catholics who need a burial place, which is located in the village of Tanjung Sawangan. Because the land was almost full, additional grave areas were needed, so expansion was carried out. Development of the tomb requires arrangement so that the tomb is neatly arranged, and becomes a comfortable place for families who will make pilgrimages. Development and arrangement are carried out in mutual cooperation and involve all Catholics, both in terms of funding and implementation. The assistance is carried out in 3 (three) stages, namely the first stage, namely preparation, the implementation stage and the third stage of reporting. The area of the grave expansion 2673 m2, with a total capacity that can be buried around 700 graves with the size of the grave (90x200)m2. Implementation took approximately 3 months and was completed as expected. The costs incurred were smaller than the budget because there were various parties who helped in the form of materials or labor.